Synthesis of Numerous Edge Sites in MoS2 via SiO2 Nanorods Platform for Highly Sensitive Gas Sensor - Shim, Young-Seok; Kwon, Ki Chang; Suh, Jun Min; Choi, Kyoung Soon; Song, Young Geun; Sohn, Woonbae; Choi, Seokhoon; Hong, Kootak; Jeon, Jong-Myeong; Hong, Seung-Pyo; Kim, Sangtae; Kim, Soo Young; et al. (American Chemical Society, 2018)
The utilization of edge sites in two-dimensional materials including transition-metal dichalcogenides (TMDs) is an effective strategy to realize high-performance gas sensors because of their high catalytic activity. Herein, we demonstrate a facile strategy to synthesize the numerous edge sites of vertically aligned MoS2 and larger surface area via SiO2 nanorod (NRs) platforms for highly sensitive NO2 gas sensor. The SiO2 NRs encapsulated by MoS2 film with numerous edge sites and partially vertical-aligned regions synthesized using simple thermolysis process of [(NH4)(2)MoS4]. Especially, the vertically aligned MoS2 prepared on 500 nm thick SiO2 NRs approximately 90 times higher gas sensing response to 50 ppm NO2 at room temperature than the MoS2 film prepared on flat SiO2, and the theoretical detection limit is as low as similar to 2.3 ppb. Additionally, it shows reliable operation with reversible response to NO2 gas without degradation at an operating temperature of 100 degrees C. The use of the proposed facile approach to synthesize vertically aligned TMDs using nanostructured platform can be extended for various TMD-based devices including sensors, water splitting catalysts, and batteries.
Keywords: ELECTROCHEMICAL SENSORS; INTERNET; THINGS; LAYERS; DEVICES